Alveolar Hemorrhage in Antineutrophil Cytoplasmic Antibody–Associated Vasculitis: Results of an International Randomized Controlled Trial (PEXIVAS) - Fussner, Lynn A.; Flores-Suárez, Luis Felipe; Cartin-Ceba, Rodrigo; Specks, Ulrich; Cox, P. Gerard; Jayne, David R. W.; Merkel, Peter A.; Walsh, Michael; Paizis, Kathy; Walters, Giles; Jardine, Meg; Milton, Caroline; et al. (American journal of respiratory and critical care medicine, 2024)
Diffuse alveolar hemorrhage (DAH) is a life-threatening manifestation of antineutrophil cytoplasmic antibody-associated vasculitis (AAV). The PEXIVAS (Plasma Exchange and Glucocorticoids in Severe Antineutrophil Cytoplasmic Antibody-Associated Vasculitis) (NCT00987389) trial was the largest in AAV and the first to enroll participants with DAH requiring mechanical ventilation. Evaluate characteristics, treatment effects, and outcomes for patients with AAV with and without DAH. PEXIVAS randomized 704 participants to plasma exchange (PLEX) or no-PLEX and reduced or standard-dose glucocorticoids (GC). DAH status was defined at enrollment as no-DAH, nonsevere, or severe (room air oxygen saturation of ⩽ 85% as measured by pulse oximetry, or use of mechanical ventilation). At enrollment, 191 (27.1%) participants had DAH (61 severe, including 29 ventilated) and were younger, more frequently relapsing, PR3 (proteinase 3)-ANCA positive, and had lower serum creatinine but were more frequently dialyzed than participants without DAH ( = 513; 72.9%). Among those with DAH, 8/95 (8.4%) receiving PLEX died within 1 year versus 15/96 (15.6%) with no-PLEX (hazard ratio, 0.52; confidence interval [CI], 0.21-1.24), whereas 13/96 (13.5%) receiving reduced GC died versus 10/95 (10.5%) with standard GC (hazard ratio, 1.33; CI, 0.57-3.13). When ventilated, ventilator-free days were similar with PLEX versus no-PLEX (medians, 25; interquartile range [IQR], 22-26 vs. 22-27) and fewer with reduced GC (median, 23; IQR, 20-25) versus standard GC (median, 26; IQR, 25-28). Treatment effects on mortality did not vary by presence or severity of DAH. Overall, 23/191 (12.0%) with DAH died within 1 year versus 34/513 (6.6%) without DAH. End-stage kidney disease and serious infections did not differ by DAH status or treatments. Patients with AAV and DAH differ from those without DAH in multiple ways. Further data are required to confirm or refute a benefit of PLEX or GC dosing on mortality. Original clinical trial registered with www.clinicaltrials.gov (NCT00987389).